The Influence of Recruitment Process on Performance and Job Satisfaction at The Dharmawangsa Jakarta - Fathin, Amirah; Ningrum, Lestari; Abas, Ahmad Junaedi (Jurnal Penelitian Pariwisata, 2018)
This study examines the influence of the recruitment process on performance and job satisfaction at The Dharmawangsa Jakarta. Recruitment process is an independent variable, while performance and job satisfaction are dependent variables. This study is explanatory research with descriptive correlation methods. The number of sample is 101 respondents. The purposive sampling technique is applied with criteria of The Dharmawangsa Jakarta. Data are collected with questionnaires and processed with data analysis. These results indicate that the reliability test was very high (0.880) and from 34 instruments statements only 1 was invalid. It showed that 101 new employees as respondents consistently answered because they understood and experienced. Each variable has a mean value of 4.11 for the recruitment process that is important for new employees, 4.16 for performance that is well, and 3.79 for job satisfaction that is new employees are satisfied. The recruitment process has a low correlation of 0.329 with performance and 0.268 with job satisfaction. The recruitment process also has a little effect of 0.8% on performance and 7.2% on job satisfaction. Based on these results, The Dharmawagsa Jakarta should improve the recruitment procedure, increase a conducive, and comfortable working atmosphere.